A Portrait of the Artist as an Angry Young Man: Masculinities and the Male Artist in Twentieth-Century British Literature - Gan, Wanghui (Université d'Ottawa / University of Ottawa, 2020)
Influenced by post-Lacanian psychoanalytic feminist theory and Judith Butler’s theories of gender performativity, this project examines three fictional brooding male writers from three separate periods of twentieth-century Ireland and Britain and their performances of authenticity, authority, and exceptionalism as artist figures. By tracing a sociohistorical arc and conducting close literary analyses, this project argues that the myth of white male artistic genius is derived from the power and privilege of a cult of individuality that can be used to excuse and justify harmful behaviour and that comes at the exclusion and expense of those outside this highly specific version of hegemonic masculinity. James Joyce’s A Portrait of the Artist as a Young Man, John Osborne’s Look Back in Anger, and Sarah Kane’s Blasted undermine the myth of male artistic genius by exposing the artificial and theatrical nature of the notion of “authenticity” and the posture of being countercultural when one is part of a dominating elite.
Keywords: Masculinities; Male Artist; Twentieth-Century British Literature; Angry Young Man